Pendidikan Islam dengan Nilai-Nilai Budaya - Susmihara Susmihara (Jurnal Adabiyah: Humanities and Islamic Studies, 2012)
Islamic education aims at educating people to be insan kamil namely, a figure who has integrity in all aspect. Thus, religious education must be socialized in early age, in order children have a basic education especially in religious aspect. Islamic education is tiedly deals with values, meanwhile culture educates some norms and moral. It means that there is close relationship between religion and culture. In this case local genuine has significant role in supporting religious education,  because it has noble values which grow from the necleus of heart.